2017
DOI: 10.1108/ejm-03-2017-0210
|View full text |Cite
|
Sign up to set email alerts
|

When does “liking” a charity lead to donation behaviour?

Abstract: Purpose: This study investigates the relationship between young people's Conspicuous Donation Behaviour (CDB) on social media platforms and their offline donation behaviour, specifically intentions to donate and volunteer time. It also explores materialism, self-esteem and self-monitoring as CDB trait antecedents, as a form of conspicuous consumption on social media. Finally, it considers the influence of altruism on these relationships. Design/Methodology: A survey was conducted of regular Facebook users ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 78 publications
1
34
1
Order By: Relevance
“…For example, for non-profit organizations, "likes" translate into donation behavior (Wallace et al, 2017).…”
Section: Consumer Engagement Via "Likes" and Commentsmentioning
confidence: 99%
“…For example, for non-profit organizations, "likes" translate into donation behavior (Wallace et al, 2017).…”
Section: Consumer Engagement Via "Likes" and Commentsmentioning
confidence: 99%
“…For instance, some may engage in pro-social behaviors out of a concern for others (altruistic orientation) or concern for self (egoistic orientation) (O'Loughlin Banks and Raciti, 2018). Others may also engage in the behavior for public recognition (Paramita et al, 2020; Wallace et al, 2017). In particular, prior research has showed that emotions can significantly influence pro-social behaviors in differential manners (O'Loughlin Banks and Raciti, 2018; Cialdini and Kenrick, 1976; Pham and Septianto, 2019; Septianto, 2020; Urbonavicius et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Being more active on social media and having a higher level of engagement with the crowd will have a positive impact on the overall funding of a crowdfunding campaign (Nevin et al, 2017). Charities and non-profit organizations recognize the value of online social media platforms for influencing consumer responses, particularly among younger consumers (Wallace et al, 2017).…”
Section: Determinants Of Individuals' Intention To Engage In Crowdfunmentioning
confidence: 99%